SINDROM NYERI KANKER: PATOFISIOLOGI DAN KLASIFIKASI KLINIS - Yusak Mangara Tua Siahaan (NEURONA, 2021)
Cancer pain is a subjective and complex complaint that is a priority in the world of oncology because it affects most aspects of the patient’s life, especially on quality of life and psychosocial responses. The recognition of cancer pain syndromes and the ability to analyze differences in the underlying pathophysiology and etiology as clinical classification are important because they determine the therapeutic and prognostic implications needed by cancer pain syndrome sufferers. Pathophysiologically, cancer pain is divided into nociceptive pain, neuropathic pain or mixed pain. Keywords: cancer pain, clinical classification, pathophysiology